Legal protection of song-creating works against piracy of musical artworks that can be downloaded for free on the website - Hartini, Sri; Radiansyah, Rama; Iskandar, Dadang; Hartono, Rudi (Technium Social Sciences Journal, 2022)
Advances in the field of technology and creativity over copyright will certainly have a negative impact that can cause considerable losses to the creator or copyright holder. The existence of violations in the field of copyright in the form of, among others, taking, quoting, broadcasting, reproducing, or announcing other people’s creations either partially or completely carried out without seizing the creator or copyright holder, will certainly be contrary to Law Number 28 of 2014 concerning Copyright. The purpose of writing this thesis is: 1) To know and analyze regarding the legal protection of song creation works against piracy of music artworks downloaded for free on the Website? and 2) To find out and analyze the inhibiting factors and efforts to carry out legal protection of song creation works against piracy of musical artworks downloaded for free on the Website. The research method used is the normative juridical method, namely by analyzing the provisions related to the problem. The results of the study found thatthe legal protection of song-creating works against piracy of music artworks downloaded for free on the Web site can be done through the steps contained in criminal law, civil law, and state administrative law. Factors are inhibiting and attempting to carry out legal protection of song creation works against piracy of musical artworks downloaded for free on the Website i.e. by preventive and repressive means.